PEMBINAAN IMAN PASCA PANDEMI VIRUS CORONA-19 BERTEMAKAN “BANGKIT JADILAH PEMENANG” KEPADA JEMAAT DI GEREJA BETHEL INDONESIA TABGHA BATAM - George Rudi Hartono Pasaribu; Steven Steven; Suhendra Suhendra (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Faith development after the corona virus pandemic-19 has proven to help the congregation to improve inward relationships with themselves. Faith that has grown can develop through the process of fostering faith, both in the family, the Church and in society. Faith coaching helps the congregation live their faithful life in a close relationship with God so that they gain meaning from the experiences of everyday life. The experience of personal relationship (relationship) with God is expected to motivate participants to be actively involved in their lives as members of the church in worship and manifested in the behavior of daily life. In the context of the church faith formation takes place in the context of worship, fellowship, teaching and service. Meanwhile, in the light of Bible teachings, all service activities in the church should be planned, directed to guide the congregation to experience coaching (learning) activities. The method used is faith development after the coronavirus-19 pandemic with the theme